Pengaruh Senam Tai Chi terhadap Psychological Wellbeing Lansia di Posyandu Sugih Waras, Desa Ngargorejo, Kecamatan Ngemplak, Boyolali - Yuniandita, Augustina Sekar; Wahyuni, Endang Sri (Jurnal Terapi Wicara dan Bahasa, 2024)
Abstract Background: Elderly people experience aging which causes changes, especially psychological, experiencing empty nest syndrome, anxiety disorders, depression, loneliness, and other psychological disorders which can affect psychological well-being. Tai Chi is an exercise that can have a positive effect on psychological well-being in sufferers of various chronic diseases, can reduce symptoms of anxiety and depression, and improve quality of life. Objectives: This study aims to determine the effect of Tai Chi exercise on the psychological well-being of elderly people at Sugih Waras Integrated Health Service Post, Ngargorejo Village, Ngemplak District, Boyolali. Methods: This research is a Pre-Experimental type of quantitative research with a one group pretest-posttest design and purposive sampling technique. Psychological well-being was measured using the Indonesian version of the 18-item Ryff Psychological Well-being Scale (RPWB). Data analysis used SPSS version 25. Results: Respondents were dominated by young elderly (73.9%), female (95.7%), housewives (91.3%), individuals with no schooling/not yet finished elementary school (47.8%), widows (69.6%), and individuals living with family (69.6%). The average pre-test and post-test RPWB scores increased by 2.53. The results of the paired sample t-test hypothesis test showed a p-value of 0.000 which is less than 0.05, indicating an influence of Tai Chi exercise on the psychological well-being of the elderly at Sugih Waras Integrated Health Service Post, Ngargorejo Village, Ngemplak District, Boyolali. Conclusion: Tai Chi exercise has an effect on the psychological well-being of the elderly at Sugih Waras Integrated Health Service Post, Ngargorejo Village, Ngemplak District, Boyolali. Keywords : Tai Chi, Psychological Well-being, Elderly